DEVELOPMENT OF LEAN AND GREEN-BASED WORK PROGRAM EVALUATION MODEL IN A COSMETIC SMALL AND MEDIUM COMPANY USING THE CIPP MODEL APPROACH - Amrina, Uly; Oktora, Adriyani; Widaningrum, Dyah Lestari (Journal of Industrial Engineering Management, 2024)
Lean and Green is well-known as an emerging paradigm in the industry to increase competitiveness with minimal environmental impact. A small and medium-sized cosmetics company in the Depok area has implemented programs based on lean and green concepts in stages since 2019. Currently, the company does not have sufficient skills and knowledge to carry out independent evaluations. The company also does not yet have a holistic and structured reference evaluation model. This research aims to assist decision-makers in SMIs in comprehensively evaluating the implementation of lean and green concepts. Researchers use the Context, Input, Process, Product (CIPP) model in the evaluation concept design with the in-depth interview (IDI) technique. The results of the study show six indicators that need improvement. Researchers propose two improvement activities that can ensure the sustainability of the lean and green program in the long term.